Systematic review of pre-clinical and clinical devices for magnetic resonance-guided radiofrequency hyperthermia. (1st January 2020) - Adibzadeh, Fatemeh; Sumser, Kemal; Curto, Sergio; Yeo, Desmond T. B.; Shishegar, Amir A.; Paulides, Margarethus M.
Abstract: Clinical trials have demonstrated the therapeutic benefits of adding radiofrequency (RF) hyperthermia (HT) as an adjuvant to radio- and chemotherapy. However, maximum utilization of these benefits is hampered by the current inability to maintain the temperature within the desired range. RF HT treatment quality is usually monitored by invasive temperature sensors, which provide limited data sampling and are prone to infection risks. Magnetic resonance (MR) temperature imaging has been developed to overcome these hurdles by allowing noninvasive 3D temperature monitoring in the target and normal tissues. To exploit this feature, several approaches for inserting the RF heating devices into the MR scanner have been proposed over the years. In this review, we summarize the status quo in MR-guided RF HT devices and analyze trends in these hybrid hardware configurations. In addition, we discuss the various approaches, extract best practices and identify gaps regarding the experimental validation procedures for MR - RF HT, aimed at converging to a common standard in this process.